Large Genomes Are Associated With Greater Cell Size and Ecological Shift Towards More Nitrogen-Rich and Higher-Latitude Environments in Microalgae of the Genus Synura - Čertnerová, Dora; Škaloud, Pavel; Jadrná, Iva; Čertner, Martin (The Journal of eukaryotic microbiology, 2025)
The nuclear genome is essential for encoding most of the genes required for cellular processes, but its size alone can alter the characteristics of cells and organisms. Yet, genome size variation and its ecological and evolutionary impacts, particularly in microorganisms, are not well understood. We used flow cytometry to estimate genome size and GC content in 53 evolutionary lineages of the microalgal genus Synura (Chrysophyceae, Stramenopiles). Genome size evolution was reconstructed in a phylogenetic framework using molecular markers. A set of genomic, morphological, and ecogeographic variables characterizing Synura lineages was evaluated and tested as predictors of genome size variation in phylogeny-corrected statistical models. Both genome size and GC content varied widely in Synura, ranging from 0.19 to 3.70 pg of DNA and 34.0% to 49.3%, respectively. Genome size variation was mainly associated with cell size, less with silica scale size, and not with scale ultrastructure. Higher soil nitrogen, higher latitudes, and lower temperatures correlated with larger genomes. Genome size evolution in Synura shows potential dynamism, with increases confined to short terminal branches, indicating lower macroevolutionary stability. Lineages with larger genomes exhibited a narrower range of suitable ecological conditions, possibly due to selection acting deleteriously against larger genomes (and cells).
Keywords: zastoupení bazí; Microalgae; flow cytometry; Genome Size; Stramenopiles; ecological requirements; délka genomu; PGLS regression; fylogeneze; Heterokontophyta; Nitrogen; Phylogeny; velikost buňky; molekulární evoluce; Evolution, Molecular; GC content; mikrořasy; evolution; Base Composition; dusík; silica scales; genome size; Cell Size